Efficient rare earth cerium(III) complex with nanosecond d−f emission for blue organic light-emitting diodes. Issue 2 (28th August 2020) - Zhao, Zifeng; Wang, Liding; Zhan, Ge; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract: In the field of RGB diodes, development of a blue organic light-emitting diode (OLED) is a challenge because of the lack of an emitter which simultaneously has a short excited state lifetime and a high theoretical external quantum efficiency (EQE). We demonstrate herein a blue emissive rare earth cerium(III) complex Ce-2 showing a high photoluminescence quantum yield of 95% and a short excited state lifetime of 52.0 ns in doped film, which is considerably faster than that achieved in typical efficient phosphorescence or thermally activated delayed fluorescence emitters (typical lifetimes >1 μs). The corresponding OLED shows a maximum EQE up to 20.8% and a still high EQE of 18.2% at 1000 cd m −2, as well as an operation lifetime 70 times longer than that of a classic phosphorescence OLED. The excellent performance indicates that cerium(III) complex could be a candidate for efficient and stable blue OLEDs because of its spin- and parity-allowed d−f transition from the Ce 3+ ion. Abstract : Unlike traditional emitters in organic light-emitting diodes (OLEDs), lanthanide cerium(III) complexes with d–f transition show simultaneously advantages of theoretical high efficiency, short excited state lifetime, adjustable emission color, and low cost.